4.9k views
23 votes
20 points

(07.04)
272226
When 27x^2z^6/-3x^2z is completely simplified, the exponent on the variable z is?

2 Answers

9 votes

Answer: 5

=========================================================

Step-by-step explanation:

Focus on the z terms only. Ignore everything else.

Up top in the numerator we have z^6

In the denominator we have z without an exponent, but it's identical to z^1

We want to divide z^6 over z^1.

Use this rule: (a^b)/(a^c) = a^(b-c)

We subtract the exponents to say (z^6)/(z^1) = z^(6-1) = z^5

User Burtlo
by
5.9k points
8 votes

Answer:

5

Step-by-step explanation:

We are looking for the exponent on z when this is simplified :
(27x^2z^6)/(-3x^2z)

In order to get this, you do not need to simplify the whole term. Looking at the numerator, we have z multiplied six times divided by one z, getting us x multiplied 5 times. Therefore the exponent on z is 5

User Max Charas
by
6.7k points